Szybkość, sprawność i efektywność postępowania cywilnego – zagadnienia podstawowe - Flaga-Gieruszyńska, Kinga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The Author presented three basic concepts related to the praxeological aspects of the course of civil proceedings. The first concept is the speed of the proceedings as a postulate counteracting the excessive length of the proceedings. The second concept is the efficiency understood as a combination of speed and proper organization of activities in the course of the proceedings aiming at a correct decision of the court. The third concept is the effectiveness, for which it is essential to achieve the goal optimally with the involvement of appropriate costs.